Association Between Thyroid-Stimulating Hormone and Renal Function: a Mendelian Randomization Study - Chi Chen; Fangzhen Xia; Yi Chen; Kun Zhang; Jing Cheng; Qin Li; Bing Han; Li Zhao; Chunfang Zhu; Ningjian Wang; Yingli Lu (Karger Publishers, 2018)
Background/Aims: Increasing evidence suggests an association between thyroid-stimulating hormone (TSH) and estimated glomerular filtration rate (eGFR). We conducted a Mendelian randomization (MR) analysis to examine the causality of the association between TSH and eGFR. Methods: 10,603 participants were recruited from the Survey on Prevalence in East China for Metabolic Diseases and Risk Factors (SPECT-China), which was performed in 23 sites in East China during 2014-2016. We constructed weighted genetic risk scores (GRS) for TSH based on three TSH-related single nucleotide polymorphisms. eGFR was calculated using the CKD Epidemiology Collaboration formula. The instrumental variable (IV) was used to explore the causal relationship between TSH and eGFR. Results: Higher measured TSH levels were associated with lower eGFR (B -0.717, 95%CI -0.958, -0.476) after multivariable adjustment. However, by MR analysis, per SD increase in the TSH_GRS was significantly associated with TSH (B 0.155, 95%CI 0.076, 0.235, P< 0.001) but not with eGFR (B -0.127, 95%CI -0.364, 0.110). Using IV estimator, no causal associations were observed for genetically instrumented TSH with eGFR. Conclusion: By a genetic approach that limits residual confounding and reverse causation in observational conventional epidemiological studies, TSH and eGFR are not causally associated, which suggests genetically elevated TSH concentrations may not affect the renal function.